2011
DOI: 10.3201/eid1705.101229
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Artesunate for Severe Malaria in Travelers, Europe

Abstract: Multicenter trials in Southeast Asia have shown better survival rates among patients with severe malaria, particularly those with high parasitemia levels, treated with intravenous (IV) artesunate than among those treated with quinine. In Europe, quinine is still the primary treatment for severe malaria. We conducted a retrospective analysis for 25 travelers with severe malaria who returned from malaria-endemic regions and were treated at 7 centers in Europe. All patients survived. Treatment with IV artesunate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 26 publications
6
107
3
9
Order By: Relevance
“…Six cases of late-onset haemolysis after AS were reported by Zoller et al among 25 travellers from seven treatment centres in Europe. 27 In those cases, haemolysis was diagnosed ,15 days after the first dose of AS; in two cases, Coombs tests were performed, and both were negative. In our patient, G6PD deficiency was excluded, but the Coombs test was positive, indicating immune-mediated haemolysis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Six cases of late-onset haemolysis after AS were reported by Zoller et al among 25 travellers from seven treatment centres in Europe. 27 In those cases, haemolysis was diagnosed ,15 days after the first dose of AS; in two cases, Coombs tests were performed, and both were negative. In our patient, G6PD deficiency was excluded, but the Coombs test was positive, indicating immune-mediated haemolysis.…”
Section: Discussionmentioning
confidence: 98%
“…We found a reduced length of stay in patients receiving AS, compared to patients treated with Q, a finding not previously documented. [27][28][29] We consider LOS is an important proxy for faster clinical recovery. The only studies looking at length of stay come from the developing world and found no reduction, which may be related to resource constraints or similar factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the effect on host cells was investigated by measuring residual cell layers by the LDH assay at 4 or 7 days after artesunate addition to confluent cells (17,51) or by measuring the LDH release in the supernatant 7 days after artesunate addition (18). Although short-term artesunate treatment is considered safe, there have been some reports on hemolytic anemia after treatment of severe malaria, but this may actually be a consequence of the severe malaria and not of artesunate (52). Even though the cytostatic effects will probably not afflict the slowly cycling epithelial cells of healthy kidneys or the urinary bladder, it may jeopardize the regeneration of epithelium damaged by PyVAN or PyVHC.…”
Section: Discussionmentioning
confidence: 99%
“…1 Compared with quinine, AS further reduces mortality resulting from severe malaria by 22.5% to 35% 2,3 and induces fewer adverse cardiac events or hypoglycemic episodes. [2][3][4][5] However, delayed anemic episodes were recently reported in 20% to 25% of travelers with severe malaria treated with AS, [6][7][8][9][10][11][12] a high, and possibly overestimated, proportion. All of these patients survived, but 60% of them required transfusions.…”
Section: Introductionmentioning
confidence: 99%